A Standardized Framework for Evaluating Surgical Enhanced Recovery Pathways: A Recommendations Statement from the TDABC in Health-care Consortium - Ana Paula B.S. Etges; Luciana Paula Cadore Stefani; Dionisios Vrochides; Junaid Nabi; Carisi Anne Polanczyk; Richard D. Urman (Journal of Health Economics and Outcomes Research)
**Background:** Innovative methodologies to redesign care delivery are being applied to increase value in health care, including the creation of enhanced recovery pathways (ERPs) for surgical patients. However, there is a lack of standardized methods to evaluate ERP implementation costs.